A Rare case of Guillain-Barré syndrome in pregnancy treated with plasma exchange - Vasudev, Rahul (Medknow Publications & Media Pvt Ltd, 2014)
Guillain-Barre syndromé (GBS) is an autoimmune disorder. It is rare in pregnancy as there is a decrease in cell-mediated immunity. A case of 28-year-old pregnant woman who presented with acute flaccid quadriplegia suffering from GBS is discussed in this study. She was treated with plasma exchange in her immediate post-partum period. The management of GBS in pregnancy has been discussed.